A cubic sphalerite structure nanocrystal and preparation method thereof

By defining the crystal structure of the nanocrystalline sphalerite structure, a relatively single ionic surface is formed, the problem of instability and inactivation of quantum dot materials in the use environment is solved, and the stability and optical properties of the material are improved.

CN119753835APending Publication Date: 2025-04-04THE GBA NAT INST FOR NANOTECHNOLOGY INNOVATION
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411950004.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

Existing quantum dot materials are prone to instability and inactivation in use environments, and existing protection methods such as inorganic shell protection and surface ligand protection have problems such as crystal structure dislocation, optical properties deterioration and high complexity.

Method used

By defining the crystal structure of the cubic sphingoite nanocrystals, the crystal structure of the {111} crystal plane family is at least 8 crystal planes with different spatial orientations, and meet the specific crystal plane area ratio or surface ion ratio, a relatively single ionic surface is formed, thereby improving the stability of the material.

Benefits of technology

The chemical properties of the material are achieved more uniform, the complexity of ligand protection is reduced, the order of subsequent shell growth is improved, and the stability of the material in terms of light resistance, heat, water and oxygen are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119753835A_ABST
    Figure CN119753835A_ABST
Patent Text Reader

Abstract

The present invention discloses a cubic sphalerite nanocrystal and a preparation method thereof, and relates to the technical field of quantum dots. The crystal structure of the cubic sphalerite nanocrystal is a cubic sphalerite structure, and the crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and satisfies at least one of the characteristics (1) and (2); characteristic (1): the proportion of the crystal plane area in the {111} crystal plane family to the total surface area of ​​the crystal structure is ≥75%, characteristic (2): the surface cation: surface anion ratio of the crystal structure is ≥4.06:1, or the surface anion: surface cation ratio is ≥4.06:1. The cubic sphalerite nanocrystal that meets the above requirements has a relatively single ion surface (basically all positive or all negative), and improves the orderliness of subsequent shell growth through a crystal plane with more uniform chemical properties, reduces the complexity of ligand protection, and is beneficial to the subsequent binding protection of a single ligand on the surface.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of quantum dots, and in particular to a cubic sphalerite structure nanocrystal and a preparation method thereof. Background Art

[0002] Quantum dots (nanocrystals) have a particle size of 2nm-20nm and a crystalline structure. Due to their excellent optical properties, such as narrow half-width, strong optical stability, continuous controllable wavelength, and high quantum efficiency, they are widely used in many fields such as display, lighting, solar energy, and bio-markers.

[0003] As the application field expands, people have found that quantum dot materials are unstable and inactivated in the use environment. A large number of domestic and foreign researchers are concerned about how to improve the stability of quantum dot materials in application scenarios. The industry mainly has the following solutions:

[0004] ①Inorganic shell protection

[0005] The quantum dot core with optical properties is protected by epitaxially encapsulating a shell with similar lattice constants (such as ZnSe outside CdSe and InP, and various gradient alloy transition layers, etc.), different band gaps (such as wide band gap materials with exciton confinement and narrow band gap materials with sacrificial layer function), and high stability (such as metal oxides, silicon oxides, boron oxides). However, when inorganic shells are grown, it often leads to dislocation of the crystal structure, degradation of the optical properties of exciton spillover (uncontrollable blue / red shift of emission wavelength, decrease in quantum efficiency, increase in emission peak width), and significant decrease in solution properties and dispersibility.

[0006] ②Surface ligand protection

[0007] In order to further stabilize the inorganic part of the quantum dot material, the ligand is directed to the cation or anion on the surface of the quantum dot by covalent bond or coordination bond. The ligands on the surface of the quantum dot can be divided into three types: L-type ligands (RNH2 and PR3 types that provide two lone pairs of electrons), X-type ligands (carboxylates, phosphates and Cl groups that provide a lone electron). – The main ligands of quantum dots are L-type ligands, X-type ligands, and Z-type ligands (long-chain carboxylates or phosphonates that can accept lone pairs of electrons). It is generally believed that quantum dot L-type ligands and X-type ligand electron donors bind to the surface cations of quantum dots to protect metal cations (such as Zn, Cd, etc.); Z-type ligands act as electron acceptors and bind to anions to protect non-metallic anions (such as Se, S, etc.). For quantum dots with different chemical activities and polar surfaces, it is necessary to introduce a variety of ligand combinations to protect them separately, which undoubtedly greatly increases the complexity and cost of the system.

[0008] ③Quantum dot complex encapsulation protection

[0009] Quantum dot composites are prepared by dispersing and encapsulating quantum dot powders or particles with high barrier materials. This method is simpler and more efficient to process a large number of quantum dot materials, and the prepared composite materials have stronger processing tolerance. Once encapsulated at the macro level, quantum dots lose their solution properties and nanoscale dispersibility, and their application range will be greatly limited.

[0010] In view of this, the present invention is proposed. Summary of the invention

[0011] The purpose of the present invention is to provide a cubic sphalerite structure nanocrystal and a preparation method thereof, so as to obtain a crystal structure with a single ion surface, thereby improving the problem that the current quantum dot material is easily destabilized and deactivated in the use environment.

[0012] The present invention is achieved in that:

[0013] In a first aspect, the present invention provides a cubic sphalerite nanocrystal, wherein the crystal structure is a cubic sphalerite structure, the crystal structure comprises at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and satisfies at least one of the characteristics (1) and (2);

[0014] Feature (1): The proportion of the crystal face area in the {111} crystal face family to the total surface area of ​​the crystal structure is ≥ 75%;

[0015] Feature (2): The ratio of surface cations to surface anions of the crystal structure is ≥4.06:1, or the ratio of surface anions to surface cations is ≥4.06:1.

[0016] In an optional embodiment, the crystal structure further includes 1 to 6 crystal planes in the {100} crystal plane family with the same or different spatial orientations.

[0017] In an optional embodiment, the crystal structure includes an octahedron, a truncated octahedron or a truncated octahedron; when the crystal structure is an octahedron, it only includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations; when the crystal structure is a truncated octahedron, it includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations and the {100} crystal plane family composed of 1-5 crystal planes with the same or different spatial orientations; when the crystal structure is a truncated octahedron, it includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations and the {100} crystal plane family composed of 6 crystal planes with the same or different spatial orientations.

[0018] In an optional embodiment, when the crystal structure is a truncated octahedron, the boundary edge length a between a crystal plane in the {111} crystal plane family and a crystal plane in the {100} crystal plane family is ≤ the boundary edge length b between one crystal plane in the {111} crystal plane family and another crystal plane in the {111} crystal plane family.

[0019] In an optional embodiment, the cubic zinc blende structure nanocrystals have a crystal size of 1-40 nm.

[0020] In an optional embodiment, the cubic sphalerite structure nanocrystal comprises a core layer and a shell layer, the composition of the core layer is at least one of a binary composition, a ternary composition and a quaternary composition; the composition of the shell layer is at least one of an inorganic substance, an organometallic compound and a high molecular polymer;

[0021] Preferably, the binary composition includes at least one of InP, InAs, GaP, AlP, CdSe, CdS, ZnSe and ZnS;

[0022] Preferably, the ternary composition includes Cd x Zn 1-x Se, Cd x Zn 1-x S, ZnSe y S 1-y and CdSe y S 1-y At least one of, wherein 0.1≤x≤0.9, 0.1≤y≤0.9;

[0023] Preferably, the quaternary composition includes Cd a Zn 1-a Se b S 1-b , where 0.1≤a≤0.9, 0.1≤b≤0.9;

[0024] Preferably, the inorganic substance comprises at least one of a sulfide, an oxide and an inorganic halide;

[0025] Preferably, the sulfide includes CdS, ZnS and Cd x Zn 1-x At least one of S;

[0026] Preferably, the oxide includes at least one of TiO2, ZnO, CdO, B2O3, Al2O3, SiO2, SnO2 and PbO;

[0027] Preferably, the inorganic halide comprises at least one of BF3, CaF2 and ZnCl2;

[0028] Preferably, the organometallic compound comprises at least one of a thiolate having 1 to 18 carbon atoms and an organic acid salt having 1 to 18 carbon atoms;

[0029] Preferably, the thiolate of 1 to 18 carbon atoms includes zinc octyl mercaptan and cadmium octyl mercaptan;

[0030] Preferably, the organic acid salt of 1 to 18 carbon atoms includes zinc oleate, zinc phthalate, zinc dodecylphosphonate, and zinc 4-alkylphenylborate;

[0031] Preferably, the relative molecular weight of the high molecular weight polymer is 5000-150000;

[0032] Preferably, the high molecular polymer includes at least one of polystyrene, polymethyl methacrylate, polycarbonate, polyethylene terephthalate, polypropylene, polysiloxane and polyamide.

[0033] In a second aspect, the present invention provides a method for preparing cubic sphalerite nanocrystals as described in any one of the aforementioned embodiments, comprising:

[0034] Adding core layer raw material liquid into the coordination solvent to prepare nearly spherical quantum dot cores;

[0035] The morphology of the quantum dot core is regulated by a kinetic regulation method or a ligand regulation method so that a polyhedron grows on the surface of the quantum dot core until the resulting crystal structure includes at least 8 crystal planes with different spatial orientations in the {111} crystal plane family, and the proportion of the crystal plane area in the {111} crystal plane family to the total surface area of ​​the crystal structure is ≥75%, and the crystal size of the cubic sphalerite structure nanocrystal is 1-40nm.

[0036] In an optional embodiment, the kinetic control method comprises dispersing the quantum dot cores in a first raw material solution, heating to 220-260° C., and adding a second raw material solution dropwise for growth for 30-360 min; preferably, the growth time is 120-360 min;

[0037] Alternatively, the ligand regulation method comprises dispersing the quantum dot cores in a first raw material solution, heating the solution to 280-320° C., and dripping a second raw material solution containing a ligand to grow the solution for 30-360 min.

[0038] In an optional embodiment, the ligand is an organic phosphonic acid;

[0039] Preferably, the organic phosphonic acid is n-octylphosphonic acid.

[0040] In an optional embodiment, the mass ratio of the ligand to the second raw material liquid is 1:8-12.

[0041] The present invention has the following beneficial effects:

[0042] The cubic sphalerite structure nanocrystals provided by the present invention are defined as cubic sphalerite structures by limiting their crystal structure to the crystal structure, and the crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and the ratio of the total surface area of ​​the crystal structure of the crystal plane area in the {111} crystal plane family is ≥75% or the ratio of the surface anions and cations is ≥4.06:1. The cubic sphalerite structure nanocrystals that meet the above requirements have a relatively single ion surface (basically all positive or all negative), and the orderliness of subsequent shell growth is improved through the crystal plane with more uniform chemical properties, the complexity of ligand protection is reduced, and it is beneficial to the subsequent binding protection of a single ligand on the surface. The present invention also provides a typical but non-limiting preparation method example, which can also obtain the above-mentioned cubic sphalerite structure nanocrystals with specific morphology by regulating its morphology through a kinetic regulation method or a ligand regulation method. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0044] Figure 1 Schematic diagrams of three possible three-dimensional structures of cubic sphalerite nanocrystals in the present invention, wherein a is an octahedron, b is a missing octahedron, and c is a truncated octahedron;

[0045] Figure 2 A schematic diagram of a 15-layer regular truncated octahedron structure used in the calculations of the present invention;

[0046] Figure 3 This is a TEM transmission electron microscope image of a 4 nm nearly spherical CdSe core obtained in step S1 of Example 1 in Experimental Example 1 of the present invention;

[0047] Figure 4 This is a TEM image of the product obtained in Comparative Example 4 in Experimental Example 1 of the present invention;

[0048] Figure 5 This is a TEM image of the product obtained in Comparative Example 5 of Experimental Example 2 of the present invention;

[0049] Figure 6 This is a TEM image of the product obtained in Example 1 of Experimental Example 2 of the present invention;

[0050] Figure 7 This is a TEM image of the product obtained in Example 3 of Experimental Example 2 of the present invention;

[0051] Figure 8 This is a TEM image of the product obtained in Example 4 of Experimental Example 2 of the present invention;

[0052] Fig. 9 This is a TEM image of the product obtained in Example 5 of Experimental Example 2 of the present invention;

[0053] Fig.10 This is a TEM transmission electron microscope image of the product obtained in Example 6 of Experimental Example 3 of the present invention when the scale is 200nm;

[0054] Fig.11 This is a TEM transmission electron microscope image of the product obtained in Example 6 of Experimental Example 3 of the present invention when the scale is 50nm;

[0055] Fig.12 This is a TEM transmission electron microscope image of the product obtained in Example 6 of Experimental Example 3 of the present invention when the scale is 20nm. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0057] The applicant of the present invention found that the catalytic activity of different crystal faces of the crystal is significantly different during research. This is mainly due to the difference in the arrangement of surface atoms on different crystal faces, and as the size is further reduced, the crystal face effect becomes more prominent and may even become the dominant factor. The same crystal growth can be regarded as an adsorption and deposition reaction catalyzed by the surface of the crystal nucleus, so the difference in crystal faces has a very direct impact on the subsequent growth and stability of the crystal.

[0058] Patent CN115701448A controls the combination of the first cation and the second anion or the first anion and the second cation on the surface of the quantum dot so that the surface of the quantum dot presents the properties of a single-charged ion. This reduces the difference between the activities of the various crystal faces of the quantum dot core, making the various crystal faces of the quantum dot core tend to be isotropic. However, there is no mention of the relevant content about the crystal structure of quantum dots, which is only generally classified as regular spheres and irregular polyhedrons, and it does not explain how the surface anions and cations tend to be distributed in a single manner from the arrangement of the exposed crystal faces.

[0059] Patent CN114956187A introduces a method for preparing a manganese trioxide catalytic material with exposed crystal faces with high catalytic activity and its application. The crystal structure morphology is regulated from the perspective of the crystal face, but its application scope is limited to manganese trioxide materials for catalytic degradation of organic pollutants, and does not involve quantum dots and nanocrystals and their application fields.

[0060] Patent CN114250074B also starts from the perspective of crystal surface stability, and obtains cubic quantum dots or quantum dots with a flat surface through direct preparation or shape transformation. And compared with non-cubic quantum dots or quantum dots before shape transformation, it has a narrower half-peak width. It only provides a relatively comprehensive protection for six-sided cubic structure quantum dots, and does not mention the surface reactivity and stability related content.

[0061] The main reason for the crystal plane effect is that the exposure degree of different atoms on the surface of binary and higher quantum dots is different. Most of the IIVI and IIIV quantum dots belong to cubic sphalerite, which is a face-centered cubic structure with cubic symmetry. The current cubic sphalerite still has the problem of poor stability in application scenarios.

[0062] Based on the above research, the present invention provides a cubic sphalerite nanocrystal, whose crystal structure is a cubic sphalerite structure, the crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and satisfies at least one of the characteristics (1) and (2);

[0063] Feature (1): The proportion of the crystal face area in the {111} crystal face family to the total surface area of ​​the crystal structure is ≥ 75%;

[0064] Feature (2): The surface cation: surface anion ratio of the crystal structure is ≥4.06:1, or the surface anion: surface cation ratio is ≥4.06:1.

[0065] It should be understood that feature (1) is limited by the crystal surface area, while feature (2) is limited by the ratio of surface anions and cations. The two have equivalent effects. Meeting any of the above features (1) and (2) can indicate that the surface of the cubic sphalerite structured nanocrystal has a single electrical ionic property and better surface ion uniformity. Compared with the existing cubic sphalerite, it has a wider range of applications and is significantly improved in terms of light / heat / water / oxygen resistance.

[0066] Among them, the {111} crystal face family represents the face of a regular octahedron, which is two upper and lower parallel faces. Specifically, the {111} crystal face family includes eight faces (111), (-111), (1-11), (11-1), (-1-11), (1-1-1), (-1-1-1), (-11-1). In the present invention, by limiting the crystal structure to have the {111} crystal face family, when the area of ​​the crystal face in the {111} crystal face family accounts for a smaller proportion, the difference in the number of anions and cations on the surface of the crystal structure will be greater. Therefore, in the present invention, the area of ​​the crystal face in the {111} crystal face family accounts for ≥75% of the total surface area of ​​the crystal structure. At this time, it can be ensured that the difference in the number of anions and cations on the surface of the crystal structure is large. At this time, the surface of the crystal structure presents a relatively single ion surface (basically all positive or all negative), and the uniformity is better.

[0067] Furthermore, the crystal structure of the present invention also includes 1-6 crystal planes of the same or different spatial orientations in the {100} crystal plane family. The 100 crystal plane family includes three spatially oriented crystal planes: (100), (010) and (001). Among them, some of the 1-6 crystal planes may have the same or different spatial orientations.

[0068] Specifically, see Figure 1 , the crystal structure includes octahedron (such as Figure 1 a), missing corner octahedron (such as Figure 1 b) or truncated octahedron (e.g. Figure 1 c); when the crystal structure is an octahedron, it only includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations; when the crystal structure is a truncated octahedron, it includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations and the {100} crystal plane family composed of 1-5 crystal planes with the same or different spatial orientations; when the crystal structure is a truncated octahedron, it includes the {111} crystal plane family composed of 8 crystal planes with different spatial orientations and the {100} crystal plane family composed of 6 crystal planes with the same or different spatial orientations.

[0069] When the crystal structure is a truncated octahedron, since the lengths of the truncated edges cannot be exactly the same, the exposure degree of the crystal faces in the {111} crystal face family and the crystal faces in the {100} crystal face family will be very different. In order to achieve a single ion surface (basically all positive or all negative), reducing the surface complexity is beneficial to the subsequent binding protection of a single ligand on the surface. In the present invention, the boundary edge length a of the crystal faces in the {111} crystal face family and the crystal faces in the {100} crystal face family is defined as ≤ the boundary edge length b of one crystal face in the {111} crystal face family and another crystal face in the {111} crystal face family. When the above boundary edge length requirements are met, in order to achieve a relatively single ion surface, it is more conducive to orderly arrangement along the crystal faces during epitaxial growth.

[0070] Furthermore, the ratio of surface cations to surface anions in the crystal structure is ≥ 4.06:1, or the ratio of surface anions to surface cations is ≥ 4.06:1. In the present invention, by limiting the ratio of surface cations to surface anions, the surface of the crystal structure is mainly a single ion, which is beneficial to the orderly arrangement along the crystal plane during subsequent epitaxial growth.

[0071] For the convenience of explanation, the following calculation is performed in the present invention:

[0072] (1) Based on a 15-layer regular truncated octahedron structure (such as Figure 2 Calculate the surface atomic ratio.

[0073] 15-layer regular truncated octahedron structure Figure 2 As shown, there are 8 111 crystal planes, and the atoms on the edges where adjacent 111 crystal planes overlap are removed. The number of crystal plane atoms is 8×(5+6+7+8+7+6+5+4)-4×12=336, and there are only single-charged ions on the 111 crystal planes. There are 6 100 crystal planes with 4×4 ions of another type outside the 5×5 structural gap, and the edges on the outer circle have been calculated into the 111 crystal planes. The number of crystal plane atoms is 6×(3×3+4×4)=150, and there are two types of ions on the 100 crystal planes with a ratio of 54:96.

[0074] Based on this, it can be calculated that there are 486 exposed atoms on the surface of the 15-layer truncated octahedron, of which the ratio of the two types of ions is 390:96≈4.06:1. It can be seen that the smaller the proportion of the truncated 100 crystal face, the greater the difference in the number of the two types of ions on the surface. For the octahedral structure containing only eight 111 crystal faces, there are only single-type ions on the surface.

[0075] (2) Calculation of surface crystal area ratio based on the regular truncated octahedron structure

[0076] Assuming that the length of each edge of the regular truncated octahedron is unit 1, the total area of ​​the 8 regular hexagonal 111 crystal faces is 12×√3; and the total area of ​​the 6 square 100 crystal faces is 6; therefore, the 111 crystal faces account for 2×√3 / (1+2×√3)≈77.6% of the total surface area.

[0077] Furthermore, in order to achieve a relatively single ion surface, epitaxial growth is more conducive to orderly arrangement along the crystal planes. The boundary length a between a crystal plane in the {111} crystal plane family and a crystal plane in the {100} crystal plane family is limited to ≤ the boundary length b between one crystal plane in the {111} crystal plane family and another crystal plane in the {111} crystal plane family.

[0078] (3) In the present invention, two extreme cases of a regular truncated octahedron are taken for analysis and comparison.

[0079] ①a=b≠0; ②b>a=0:

[0080] ① Under the condition that the lengths of the edges are equal and close to a sphere, the proportion of the 111 crystal plane to the total surface area is: 2×√3 / (1+2×√3)≈77.6%. At this time, the ratio of the two types of ions is about 4.06:1. This is the minimum limit for maintaining the surface ion homogeneity, and it is the lower limit. It should be understood that 77.6% is calculated as a typical but non-limiting example (a regular truncated octahedron). When the crystal structure changes, the calculated data may have a certain deviation. Therefore, the present invention defines the proportion of the 111 crystal plane to the total surface area as ≥75%, which means that the ion homogeneity on the surface of the crystal structure is considered to be better.

[0081] ② Under the condition a=0, the 100 crystal plane does not exist, and only the 111 crystal plane accounts for 100%. It is also known that there are only ions of one electrical property on the 111 crystal plane, so under this condition, there is the singlest ion surface, which is the upper limit.

[0082] Therefore, the present invention stipulates that: the ratio of the crystal face area in the {111} crystal face family to the total surface area of ​​the crystal structure is ≥75%, or it can be expressed as: the surface cations: surface anions of the crystal structure is ≥4.06:1, or the surface anions: surface cations ≥4.06:1. Meeting the above requirements can achieve better ionic uniformity on the surface of the crystal structure.

[0083] Furthermore, the crystal size of cubic sphalerite nanocrystals is 1-40 nm, and the crystal size presents a nanostructure.

[0084] In addition, it should be noted that the cubic sphalerite nanocrystals in the present invention may also be a single core structure, or may include a core layer and a shell layer, wherein the composition of the core layer is at least one of a binary composition, a ternary composition, and a quaternary composition; and the composition of the shell layer is at least one of an inorganic substance, an organometallic compound, and a high molecular polymer.

[0085] Preferably, the binary composition includes at least one of InP, InAs, GaP, AlP, CdSe, CdS, ZnSe and ZnS; the ternary composition includes Cd x Zn 1-x Se, Cd x Zn 1-x S, ZnSe y S 1-y and CdSe y S 1-y At least one of the following, wherein 0.1≤x≤0.9, 0.1≤y≤0.9; the quaternary composition includes Cd a Zn 1-a Se b S 1-b , where 0.1≤a≤0.9, 0.1≤b≤0.9.

[0086] Preferably, the inorganic substance includes at least one of sulfide, oxide and inorganic halide; sulfide includes CdS, ZnS and Cd x Zn 1-x S; the oxide includes at least one of TiO2, ZnO, CdO, B2O3, Al2O3, SiO2, SnO2 and PbO; the inorganic halide includes at least one of BF3, CaF2 and ZnCl2.

[0087] Preferably, the organometallic compound includes at least one of a thiolate of 1-18 carbon atoms and an organic acid salt of 1-18 carbon atoms; the thiolate of 1-18 carbon atoms includes zinc octyl mercaptan and cadmium octyl mercaptan; the organic acid salt of 1-18 carbon atoms includes zinc oleate, zinc phthalate, zinc dodecylphosphonate, and zinc 4-alkylphenylborate.

[0088] Preferably, the relative molecular weight of the high molecular polymer is 5000-150000; the high molecular polymer includes at least one of polystyrene, polymethyl methacrylate, polycarbonate, polyethylene terephthalate, polypropylene, polysiloxane and polyamide.

[0089] In addition, the present invention also provides a method for preparing the above-mentioned cubic sphalerite structure nanocrystals, which comprises the following steps:

[0090] S1. Adding core layer raw material liquid into the coordination solvent to prepare a nearly spherical quantum dot core.

[0091] In the present invention, a conventional method can be used to prepare quantum dot cores, such as a typical hot injection method. Taking the preparation of a nearly spherical CdSe core as an example, the method includes heating 60mL of 0.75mmol / mL oleic acid cadmium solution to 340°C in a coordination solvent (1-octadecene ODE, trioctylamine TOA) under argon protection, quickly adding 20mL of 2mmol / mL TOP-Se solution, and cooling the sample after 1 minute to obtain a 4nm nearly spherical CdSe core. It should be understood that any method that can prepare a nearly spherical quantum dot core can be used as step S1 in the present invention.

[0092] S2. The morphology of the quantum dot core is controlled by a kinetic control method or a ligand control method so that a polyhedron grows on the surface of the quantum dot core, until the resulting crystal structure includes at least 8 crystal planes with different spatial orientations in the {111} crystal plane family, and the proportion of the crystal plane area in the {111} crystal plane family to the total surface area of ​​the crystal structure is ≥75%, and the crystal size of the cubic sphalerite structure nanocrystals is 1-40nm.

[0093] The kinetic control method comprises dispersing the quantum dot cores in a first raw material solution, heating to 220-260° C., and dripping a second raw material solution for growth for 30-360 minutes; the preferred growth time is 120-360 minutes.

[0094] Alternatively, the ligand regulation method includes dispersing the quantum dot core in a first raw material liquid, heating to 280-320°C, and dripping a second raw material liquid containing a ligand for 30-360 minutes. The ligand is an organic phosphonic acid; preferably, the organic phosphonic acid is n-octylphosphonic acid. The mass ratio of the ligand to the second raw material liquid is 1:8-12.

[0095] Among them, the selection of the first raw material liquid and the second raw material liquid needs to be determined according to the composition of the cubic sphalerite structure nanocrystals to be prepared. When the cubic sphalerite structure nanocrystals have no shell layer, the first raw material liquid and the second raw material liquid can select the same raw material as the preparation of the quantum dot core; when the cubic sphalerite structure nanocrystals have a shell layer, the first raw material liquid and the second raw material liquid can select the material corresponding to the above shell material. Since the nearly spherical quantum dot core cannot distinguish the crystal plane, the core point of the present invention is to regulate the outer surface of the quantum dot core so that its outer surface forms a distinct {111} crystal plane family, and at least 8 crystal planes with different spatial orientations in the {111} crystal plane family, and the proportion of the crystal plane area in the {111} crystal plane family to the total surface area of ​​the crystal structure is ≥75%.

[0096] It should be understood that kinetic growth in crystal growth refers to the phenomenon that the growth rate of the epitaxial layer is controlled by reaction kinetic factors, and the growth rate is related to the growth temperature (low temperature) and substrate orientation. The atoms are arranged and stacked in an orderly manner according to the designed structure, and this phenomenon is called kinetic controlled growth.

[0097] In addition, thermodynamic conditions are equally important in crystal growth. Crystal growth theory is used to explain the physical-chemical process of crystal growth. The parent phase that forms the crystal can be gas, liquid or solid. The growth process can be achieved in nature or under artificial control. The driving forces of crystal growth include temperature (high temperature) gradient, concentration gradient and stress, etc. These factors affect the nucleation and growth rate of crystals through thermodynamic principles.

[0098] Taking the above-mentioned kinetic regulation method or ligand regulation method as an example, at a lower temperature, the growth is kinetically regulated and tends to form an octahedral structure with 8 111 crystal faces. At a higher nucleation growth temperature, the growth is thermodynamically regulated and tends to form a truncated octahedral near-spherical structure with higher thermodynamic stability. Among them, the temperature of the kinetic regulation method is lower than that of the ligand regulation method. This is because in the kinetic regulation method, if the temperature is too high, irregular heterogeneous structures will appear on the surface. After adding the ligand, the growth can still be regulated to obtain octahedral grains with 8 111 crystal faces even at a higher temperature.

[0099] The principle is that after the ligand binds to cations such as Cd and Zn, it will reduce the ability of the cations to bind to anions Se and S, increase the activation energy of the nanocrystal growth reaction and reduce the reaction rate. Even at high temperatures, the reaction still follows the low-temperature kinetic control law. The addition of strong organic phosphonic acid ligands reduces the mobility of cations (essentially making the kinetic and thermodynamic product conversion irreversible), such as Figure 1 As shown, controlling different main products is not possible with any parallel reaction, but only with reactions that meet certain conditions. Figure 1 Take the example of A generating two products, B and C, respectively: if the reactions in both directions are almost irreversible, once B and C are generated, they cannot be reversed, and there is no balance. Until the reactants are consumed, it is obvious that the one with the fastest generation rate has the largest amount, then the main products are all kinetically controlled products.

[0100] The above-mentioned kinetic regulation method or ligand regulation method is based on the nanocrystal growth model. The characteristic of the scope of application is to regulate the "growth" process of nanocrystals from "small to large". In this process, compounds with the same cubic sphalerite structure are deposited on the crystal surface in an orderly manner according to the crystal plane orientation. Thereby forming an octahedral or truncated octahedral structure with the characteristics of the {111} crystal face family and the {100} crystal face family. Crystals with a larger proportion of {111} crystal faces have a more single ionic surface (basically all positive or all negative), which reduces the surface complexity and is conducive to the subsequent binding protection of a single ligand on the surface.

[0101] At present, there is another means of regulating the crystal morphology of nanomaterials, which is etching. The etching method is to first prepare a large crystal, and then peel off the surface atoms through chemical, physical and other methods. Adjust its crystal morphology and the degree of exposure of the crystal face. As the etching proceeds, the crystal size "decreases from large to small". The specific etching method is a publicly available document and can also achieve the same purpose. However, it is different from the growth regulation of the present invention. The present invention uses the growth process to regulate the morphology of the crystal, thereby obtaining a cubic sphalerite structure with a certain 111 crystal face ratio.

[0102] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0103] Example 1

[0104] This embodiment provides a cubic sphalerite nanocrystalline CdSeS, and the preparation method thereof includes:

[0105] S1. Under argon protection, 60 mL of 0.75 mmol / mL cadmium oleate solution was heated to 340 °C in a coordination solvent (1-octadecene ODE, trioctylamine TOA), and 20 mL of 2 mmol / mL TOP-Se solution was quickly added. After 1 minute, the sample was cooled to obtain a 4 nm nearly spherical CdSe core (such as Figure 3 shown).

[0106] S2, take 4nm nearly spherical CdSe cores and disperse them into 0.25mmol / mL cadmium oleate TOA solution, slowly add 20mL of TOP-S solution at a growth temperature of 240℃ for reaction, and the addition time is 30min. After the addition is completed, the size of the obtained cubic sphalerite structure nanocrystalline CdSeS is 6nm, and the morphology is nearly spherical particles doped with a small amount of polyhedrons (such as Figure 6 shown).

[0107] Example 2

[0108] This embodiment provides a cubic sphalerite nanocrystalline CdSeS, and the preparation method thereof includes:

[0109] S1. Under argon protection, heat 60 mL of 0.75 mmol / mL cadmium oleate solution to 340 °C in a coordination solvent (1-octadecene ODE, trioctylamine TOA), quickly add 20 mL of 2 mmol / mL TOP-Se solution, and cool the sample after 1 minute to obtain a 4 nm nearly spherical CdSe core.

[0110] S2. Take 4nm nearly spherical CdSe cores and disperse them in 0.25mmol / mL cadmium oleate TOA solution. Slowly add 20mL of TOP-S solution containing n-octylphosphonic acid ligands at a growth temperature of 300℃ for reaction. The addition time is 30min. The mass ratio of TOP-S solution containing n-octylphosphonic acid ligands is 1:10. After the addition is completed, the cubic sphalerite structure nanocrystalline CdSeS morphology obtained has polyhedral edges.

[0111] Experimental Example 1: Investigating the effect of growth temperature on morphology

[0112] Comparative Examples 1-4 were obtained by adjusting the growth temperature in Example 1.

[0113] Comparative Example 1: This comparative example is basically the same as Example 1, except that the growth temperature in Example 1 is replaced with 120°C.

[0114] Comparative Example 2: This comparative example is basically the same as Example 1, except that the growth temperature in Example 1 is replaced with 180°C.

[0115] Comparative Example 3: This comparative example is basically the same as Example 1, except that the growth temperature in Example 1 is replaced with 300°C.

[0116] Comparative Example 4: This comparative example is basically the same as Example 1, except that the growth temperature in Example 1 is replaced with 340°C (as Figure 4 shown).

[0117]

[0118]

[0119] As can be seen from the above table, when the temperature is lower than the range of 220-260°C, it will cause the nearly spherical particles to almost not grow, and it will not play a good role in morphology regulation. When the temperature is higher than the range of 220-260°C, it will cause the nearly spherical particles to have a significant increase in size or an irregular surface heterostructure, which is not conducive to the construction of the cubic sphalerite structure nanocrystals containing the {111} crystal plane family of the present invention. Among them, although the nearly spherical size in Comparative Example 3 has increased, its morphology is still nearly spherical, and the regulation of 111 and 100 crystal planes has not been achieved. In Comparative Example 4, the surface presents an irregular heterostructure, and it is impossible to judge the 111 and 100 crystal planes. Therefore, it is impossible to calculate the proportion of anions and cations.

[0120] Experimental Example 2: Investigating the effect of growth time on morphology

[0121] By adjusting the growth time of Example 1, Examples 3-5 were obtained.

[0122] Comparative Example 5: This comparative example is basically the same as Example 1, except that the growth time in Example 1 is replaced with 0 min, that is, the regulation step of step S2 is not performed, and only the nearly spherical CdSe core of step S1 is used as the final product (such as Figure 5 shown).

[0123] Example 3: This comparative example is basically the same as Example 1, except that the growth time in Example 1 is replaced by 60 min (as Figure 7 shown).

[0124] Example 4: This comparative example is basically the same as Example 1, except that the growth time in Example 1 is replaced by 90 min (as Figure 8shown).

[0125] Example 5: This comparative example is basically the same as Example 1, except that the growth time in Example 1 is replaced by 180 min (as Fig. 9 shown).

[0126]

[0127]

[0128] It can be seen from the above table that when the growth time is too short, it cannot play a regulatory role. As the growth time increases, the edges and corners become more obvious, which is more conducive to the preparation of octahedral structure.

[0129] Experimental Example 3: Investigating the effects of ligand usage and reaction time on morphology

[0130] By adjusting the selection, dosage and reaction time of the ligand in Example 2, Comparative Examples 6-9 and Example 6 were obtained.

[0131] Comparative Example 6: This comparative example is basically the same as Example 2, except that the ligand in Example 2 is omitted.

[0132] Comparative Example 7: This comparative example is substantially the same as Example 2, except that the mass ratio of the TOP-S solution of the n-octylphosphonic acid ligand in Example 2 is modified to 1:20.

[0133] Comparative Example 8: This comparative example is substantially the same as Example 2, except that the mass ratio of the TOP-S solution of the n-octylphosphonic acid ligand in Example 2 is modified to 1:5.

[0134] Comparative Example 9: This comparative example is basically the same as Example 2, except that the n-octylphosphonic acid ligand in Example 2 is changed to dodecylbenzeneboric acid.

[0135] Example 6: This example is substantially the same as Example 2, except that the reaction time in Example 2 is modified to 360 min (eg Fig.10 , Fig.11 and Fig.12 shown).

[0136]

[0137]

[0138] It can be seen from the above table that when no ligand is used, it cannot play a regulatory role under high temperature conditions. At the same time, when the amount of ligand is too small, it cannot play a regulatory role. When the amount of ligand is too large, irregular morphology will appear. Choosing other ligands will not play a regulatory role. By extending the reaction time, the octahedral structure of the morphology can be improved.

[0139] Experimental Example 4: Light Attenuation Experiment

[0140] The experimental method includes: taking an appropriate amount of quantum dot solution and diluting it with octane, controlling the absorption of the solution to be tested to be between 50% and 75%. Using a 405nm light power density of 2000W / m 2 The blue light was continuously irradiated and the change of quantum yield over time was measured using an integrating sphere.

[0141]

[0142] It can be seen from the above table that as the proportion of 111 crystal plane increases, the light attenuation amplitude decreases significantly.

[0143] Experimental Example 5: Water / Heat / Oxygen Experiment (Solution Method)

[0144] The experimental method includes: preparing an aqueous solution according to the mass fraction of 0.125% quantum dots, 0.75% oxygen free radical initiator benzoyl peroxide, and 0.625% emulsifier Tween-80. Place it in an ultrasonic emulsifier for emulsification for 3 minutes (amplifier Φ10, power 50%, ultrasound for 2s and stop for 4s, and the probe is inserted into the liquid surface about 1cm). The emulsified system is placed at 80℃ and stirred continuously, and the change of the emulsion quantum yield over time is measured using an integrating sphere. In this test example, aqueous solution, continuous heating at 80℃, and oxygen free radical initiator benzoyl peroxide are used to simulate the water, heat, and oxygen environments respectively, and the stability of different quantum dots in them is evaluated.

[0145]

[0146]

[0147] It can be seen from the above table that as the proportion of 111 crystal plane increases, the attenuation of quantum yield affected by hydrothermal oxygen is significantly reduced.

[0148] In summary, the cubic sphalerite nanocrystals provided by the present invention are defined as cubic sphalerite structures by limiting their crystal structure to the crystal structure, the crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and the proportion of the total surface area of ​​the crystal structure of the crystal plane area in the {111} crystal plane family is ≥75%, and the crystal size of the cubic sphalerite nanocrystals is 1-40nm. The cubic sphalerite nanocrystals that meet the above requirements have a relatively single ionic surface (basically all positive or all negative), and the orderliness of subsequent shell growth is improved by a crystal plane with more uniform chemical properties, and the complexity of ligand protection is reduced, which is conducive to the subsequent binding protection of a single ligand on the surface. The present invention also provides a typical but non-limiting preparation method example, which can also obtain the above-mentioned cubic sphalerite nanocrystals with a specific morphology by regulating its morphology through a kinetic regulation method or a ligand regulation method.

[0149] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A cubic sphalerite structure nanocrystal, characterized in that: The crystal structure is a cubic sphalerite structure, the crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family, and satisfies at least one of the characteristics (1) and (2); Feature (1): The proportion of the crystal face area in the {111} crystal face family to the total surface area of ​​the crystal structure is ≥ 75%; Feature (2): The ratio of surface cations to surface anions of the crystal structure is ≥4.06:1, or the ratio of surface anions to surface cations is ≥4.06:

1.

2. The cubic sphalerite structure nanocrystal according to claim 1, characterized in that: The crystal structure further includes 1 to 6 crystal planes in the {100} crystal plane family with the same or different spatial orientations.

3. The cubic sphalerite structure nanocrystal according to claim 2, characterized in that: The crystal structure includes an octahedron, a truncated octahedron or a truncated octahedron; when the crystal structure is an octahedron, it only includes a {111} crystal plane family composed of 8 crystal planes with different spatial orientations; when the crystal structure is a truncated octahedron, it includes a {111} crystal plane family composed of 8 crystal planes with different spatial orientations and a {100} crystal plane family composed of 1-5 crystal planes with the same or different spatial orientations; when the crystal structure is a truncated octahedron, it includes a {111} crystal plane family composed of 8 crystal planes with different spatial orientations and a {100} crystal plane family composed of 6 crystal planes with the same or different spatial orientations.

4. The cubic sphalerite structure nanocrystal according to claim 3, characterized in that: When the crystal structure is a truncated octahedron, the boundary side length a between a crystal plane in the {111} crystal plane group and a crystal plane in the {100} crystal plane group is ≤ the boundary side length b between one crystal plane in the {111} crystal plane group and another crystal plane in the {111} crystal plane group.

5. The cubic sphalerite structure nanocrystal according to claim 1, characterized in that: The crystal size of the cubic sphalerite structure nanocrystal is 1-40 nm.

6. The cubic sphalerite structure nanocrystal according to claim 1, characterized in that: The cubic sphalerite nanocrystal comprises a core layer and a shell layer, wherein the composition of the core layer is at least one of a binary composition, a ternary composition and a quaternary composition; and the composition of the shell layer is at least one of an inorganic substance, an organometallic compound and a high molecular polymer; Preferably, the binary composition includes at least one of InP, InAs, GaP, AlP, CdSe, CdS, ZnSe and ZnS; Preferably, the ternary composition includes Cd x Zn 1-x Se, Cd x Zn 1-x S, ZnSe y S 1-y and CdSe y S 1-y At least one of, wherein 0.1≤x≤0.9, 0.1≤y≤0.9; Preferably, the quaternary composition includes Cd a Zn 1-a Se b S 1-b , where 0.1≤a≤0.9, 0.1≤b≤0.9; Preferably, the inorganic substance comprises at least one of a sulfide, an oxide and an inorganic halide; Preferably, the sulfide includes CdS, ZnS and Cd x Zn 1-x At least one of S; Preferably, the oxide includes at least one of TiO2, ZnO, CdO, B2O3, Al2O3, SiO2, SnO2 and PbO; Preferably, the inorganic halide comprises at least one of BF3, CaF2 and ZnCl2; Preferably, the organometallic compound comprises at least one of a thiolate having 1 to 18 carbon atoms and an organic acid salt having 1 to 18 carbon atoms; Preferably, the thiolate of 1 to 18 carbon atoms includes zinc octyl mercaptan and cadmium octyl mercaptan; Preferably, the organic acid salt of 1 to 18 carbon atoms includes zinc oleate, zinc phthalate, zinc dodecylphosphonate, zinc 4-alkylphenylborate; Preferably, the relative molecular weight of the high molecular weight polymer is 5000-150000; Preferably, the high molecular polymer includes at least one of polystyrene, polymethyl methacrylate, polycarbonate, polyethylene terephthalate, polypropylene, polysiloxane and polyamide.

7. A method for preparing cubic sphalerite nanocrystals according to any one of claims 1 to 6, characterized in that: It includes: Adding core layer raw material liquid into the coordination solvent to prepare nearly spherical quantum dot cores; The morphology of the quantum dot core is regulated by a kinetic regulation method or a ligand regulation method so that a polyhedron grows on the surface of the quantum dot core until the resulting crystal structure includes at least 8 crystal planes of different spatial orientations in the {111} crystal plane family and satisfies at least one of the characteristics (1) and (2).

8. The method for preparing cubic sphalerite nanocrystals according to claim 7, characterized in that: The kinetic control method comprises dispersing the quantum dot cores in a first raw material solution, heating to 220-260° C., and dripping a second raw material solution for growth for 30-360 min; preferably, the growth time is 120-360 min; Alternatively, the ligand regulation method comprises dispersing the quantum dot cores in a first raw material solution, heating the solution to 280-320° C., and dripping a second raw material solution containing a ligand to grow the solution for 30-360 min.

9. The method for preparing cubic sphalerite nanocrystals according to claim 8, characterized in that: The ligand is an organic phosphonic acid; Preferably, the organic phosphonic acid is n-octylphosphonic acid.

10. The method for preparing cubic sphalerite nanocrystals according to claim 8, characterized in that: The mass ratio of the ligand to the second raw material liquid is 1:8-12.